Directions for clinical practice improvement in HFE gene mutation testing - Gillett, M.; Marmotte, Cyril; Ravine, D.; Vasikaran, S. (Australian Medical Association, 2007)
Objective: To audit the clinical indications for HFE gene mutation testing in a consecutive series of requests.Design: Retrospective audit of reasons prompting 187 HFE test requests received between June 2003 and June 2005, by examination of the request form, hospital notes (when available) and, when required, information from the referring doctor.Setting: A tertiary care public teaching hospital laboratory, Perth, Western Australia.Main outcome measures: Reasons prompting requests for HFE genotype testing and compliance with accepted clinical indications (biochemical evidence of iron overload on repeated samples, or a first-degree relative with either haemochromatosis or a C282Y mutation).Results: Insufficient clinical details in requests prevented the inclusion of interpretive comments in HFE genotype reports in 70 of 187 cases (37%). Re-evaluation after collation of the missing details for all but seven requests revealed that 103 of the 180 auditable requests (57%) had been prompted for reasons other than biochemical evidence of iron accumulation or family history.Conclusions: A substantial proportion of HFE genotype test requests are made for inappropriate reasons. Clinical practice could be improved by educating doctors on the practical utility of this genetic test and by laboratories taking steps to secure the clinical information needed to include appropriate interpretive comments in their reports.